2004
DOI: 10.1044/1092-4388(2004/102)
|View full text |Cite
|
Sign up to set email alerts
|

Tense and Agreement in the Speech of Children With Specific Language Impairment

Abstract: Thirty-one children with specific language impairment participated in 48 intervention sessions designed to assist them in the use of 3rd-person singular -s or auxiliary is/are/was. Gains in the use of these target forms were significantly greater than gains on developmentally comparable morphemes serving as control forms. Untreated verb forms that mark both tense and agreement showed greater change during the intervention period than did past -ed. The findings suggest that by gaining skill in the use of morphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 34 publications
5
108
1
2
Order By: Relevance
“…Cleave, Becker, Curran, Van Horne, & Fey, 2015). Several treatment studies reported in the language intervention literature provide evidence that supports the basic efficacy of conversational recast treatment for targeting morphosyntax in preschool-age children (e.g., Camarata & Nelson, 1992;Camarata, Nelson, & Camarata, 1994;Leonard, Camarata, Brown, & Camarata, 2004;Leonard, Camarata, Pawlowska, Brown, & Camarata, 2006;Nelson, Camarata, Welsh, Butkovsky, & Camarata, 1996). Conversational recast is a promising treatment that may be improved to further increase the efficacy or efficiency of the procedure.…”
Section: Conversational Recast Treatmentmentioning
confidence: 99%
“…Cleave, Becker, Curran, Van Horne, & Fey, 2015). Several treatment studies reported in the language intervention literature provide evidence that supports the basic efficacy of conversational recast treatment for targeting morphosyntax in preschool-age children (e.g., Camarata & Nelson, 1992;Camarata, Nelson, & Camarata, 1994;Leonard, Camarata, Brown, & Camarata, 2004;Leonard, Camarata, Pawlowska, Brown, & Camarata, 2006;Nelson, Camarata, Welsh, Butkovsky, & Camarata, 1996). Conversational recast is a promising treatment that may be improved to further increase the efficacy or efficiency of the procedure.…”
Section: Conversational Recast Treatmentmentioning
confidence: 99%
“…In the first study (Leonard et al, 2004), it was observed that after 48 intervention sessions, both the 3S and AUX children made significantly greater gains in the use of their respective target morphemes than on the other morphemes being monitored. In addition, each group showed greater use of both third singular -s and auxiliary is/are/was than another tenserelated morpheme being monitored, past tense -ed.…”
mentioning
confidence: 99%
“…The first two phases were presented in this Journal by Leonard, Camarata, Brown, and Camarata (2004) and Leonard, Camarata, Pawłowska, Brown, and Camarata (2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The children in their studies made greater gains in use of the grammatical target after 10 months of treatment than the children who received treatment for 5 months. In addition, Leonard, Camarata, Brown, and Camarata (2004) and Leonard et al (2006) used conversational recast treatment for a total of 48 sessions over 3 months, and then continued to a total of 96 intervention sessions over 6 months. Children showed modest gains after 3 months but continued to improve with additional time.…”
Section: Discussionmentioning
confidence: 99%